Um framework para o controle e a supervisão de processos avícolas - Lorencena, Mainara Cristina (2018)
Poultry management is a judicious activity to be carried out in poultry farms. In it are inserted tasks like maintenance of hygiene, sanity and, mainly, ambience control. Tem- perature and humidity are the main parameters for achieving thermal equilibrium. However, most ambience control systems for aviaries available on the market don’t have the desirable efficiency, characterized by the maintenance of temperature and humidity and maximum possible homogenization of these variables throughout the environment. Instead, what is observed is that, even in the presence of semiautomatic control systems, the main management decisions still depend on the expert’s perception (aviculturist) to observe the process and configure the parameters of the controller. In addition to being inefficient, this activity is also cumbersome and prone to errors. This dissertation proposes a framework for control, supervision and decision making in poultry process. Initially, it is systematized the collection of a set of events related to temperature and humidity, in order to provide more details about the internal climatic conditions of the aviary. From this, the modeling and control synthesis steps are presented based on the Supervisory Control Theory (TCS), in its monolithic and modular versions, which are compared, and give support the physical implementation in microcontroller. The advantages of the approach chosen in relation to the homo- genization of temperature and humidity in aviaries are illustrated by simulation and compared to a traditional management scenario. Final results still provide a remote process supervision option using a SCADA tool.